Upper intermediate Arabic through discussion : 20 lessons on contemporary topics with integrated skills and fluency-building activities for MSA learners - Korica, Nevenka (The American University in Cairo Press, 2023)
"Upper-Intermediate Arabic through Discussion is a classroom-tested course that uses an inquiry-based approach to challenge intermediate learners of Arabic by engaging them in thought provoking discussions about topics of general interest. Each topic is stated in the form of a question, such as "What is the best way to learn a foreign langue?" or" Why are some sports more popular than others?," to prod students to immediately start searching for an answer. Drawing on her long experience as an Arabic instructor, Nevenka Korica Sullivan has organized the book into twenty chapters, each one devoted to a single theme. While exploring each topic, learners are guided to expand their vocabulary, acquire more complex structures, and discover systemic relationships between language form, function, and meaning. A rich assortment of exercises and activities ensures that learners make palpable progress toward advancing their language skills. The course is designed to create a lively learner-centered classroom where interaction between participants is both the goal and the means of language study; it can also be successfully used with a tutor or for independent study."--